DIRECTIONS OF ECONOMIC REFORMS FOR THE DEVELOPMENT OF SUPPLY NETWORK COMPANIES IN THE REPUBLIC - Tleubergenov R. Sh.; Kadirbergenov M. O.; Baltabayev M. P. (Web of Journals Publishing, 2024)
In the article, in the context of the transition to the market economy and market reforms, it is appropriate to achieve business and private entrepreneurship and economic indicators. A real businessman who decides to do business in any business should be prepared to take risks by identifying the dangerous aspects of his actions. At that point, the supply systems are integrated into the service systems for the at-risk population. In the past, entrepreneurship was an auxiliary sector of the economy, but in recent years it has gained a strategic reputation in the republic.
Keywords: reforms, business, insurance, market, firm, economy, standard, capital, company.